Potentiation of Synedrella nodiflora L. For Insecticidal Activity, Insect Repellency and Brine Shrimp Lethality in the Laboratory Conditions - Abdullah, Moniruzzaman Mohammad; Islam, Nurul (Journal of Life and Earth Science, 2014)
The insecticidal activity, insect repellency and brine shrimp lethality tests of three solvent extracts of Synedrella nodiflora L. were assessed against the adults of Tribolium castaneum (Herbst) under laboratory conditions. The methanol extract found most effective (LD50 1.229, 0.823 and 0.569mg cm-2 for 24, 36 and 48h of exposure respectively) followed by the chloroform extract (LD50 3.042, 2.773, 2.456 and 2.233mg cm-2 for 12, 24, 36 and 48h of exposure respectively) and petroleum ether extract (LD50 8.416, 4.764, 3.677, 3.392 and 3.177mg cm-2 for 12, 24, 36, 48 and 60h exposure respectively). The CHCl3 and MeOH extracts showed repellent activity against T. castaneum adults at P<0.05 and P<0.01 levels of significance, while the Pet. E. extract did not show any repellency. The similar extracts responded through brine shrimp lethality assay and the Pet. E. extract found most effective (LC50 321.182, 248.151, 182.196 and 140.866ppm) followed by the MeOH extract (LC50 428.356, 72.401, 68.397 and 22.161ppm for 12, 18, 24 and 30h of exposure respectively) and the CHCl3 extract (LC50 669.875, 416.605, 288.226 and 248.325ppm). The results show the potential of using the S. nodiflora extracts for T. castaneum suppression. DOI: http://dx.doi.org/10.3329/jles.v7i0.20125 J. Life Earth Sci., Vol. 7: 79-82, 2012